The Complete Practitioner's Guide to the Bond Market (McGraw-Hill Finance & Investing) - I. Dym Steven (MC Graw Hill, 2010)
Speaking directly to the practitioner, this thorough guide covers everything there is to know about bonds—from basic concepts to more advanced bond topics.